11.7k views
3 votes
Solve for x.
7(1x - 3) = 4(x + 5)

User DapperDuck
by
5.4k points

1 Answer

5 votes

Answer:

x = 41/3

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define equation

7(1x - 3) = 4(x + 5)

Step 2: Solve for x

  1. Simplify: 7(x - 3) = 4(x + 5)
  2. Distribute: 7x - 21 = 4x + 20
  3. Subtract 4x on both sides: 3x - 21 = 20
  4. Add 21 on both sides: 3x = 41
  5. Divide 3 on both sides: x = 41/3

Step 3: Check

Plug in x to verify it's a solution.

  1. Substitute: 7(1(41/3) - 3) = 4(41/3 + 5)
  2. Multiply: 7(41/3 - 3) = 4(41/3 + 5)
  3. Subtract/Add: 7(32/3) = 4(56/3)
  4. Multiply: 224/3 = 224/3

Here, we see that 224/3 is indeed equivalent to 224/3. ∴ x = 41/3 is a solution to the equation.

And we have our final answer!

User Jocelyn LECOMTE
by
5.3k points